The Analysis of Marketing Efficiency of Siompu Oranges in Siompu District - Sulastina Sulastina; Surni Surni; Rosmawaty Rosmawaty (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2023)
This research aims to determine the marketing channel patterns, analyse the marketing margins, and assess the marketing efficiency of Siompu oranges. The Simple Random Sampling technique will be used to ascertain the sample for the investigation. The participants and marketing firms in this research were selected via Snowball Sampling. The sample consisted of 34 farmers, 5 collectors, and 7 shopkeepers. The findings indicated the existence of two marketing channels for Siompu oranges in Siompu District: marketing channel I, which involves producers, collectors, and merchants and ultimately reaches the end customers. Marketing channel II begins with farmers and merchants and then promotes directly to end customers. The cost per kilogram in Marketing Channel I is IDR 1,398.69, while in Marketing Channel II it is IDR 323.69. The total margin per kilogram in Marketing Channel I is IDR 10,000, while in Marketing Channel II, it is IDR 5,000. The proportion of the farmers' share in Marketing Channel I is 80%, while in Marketing Channel II, it is 90%